A comparative study of spring avifauna in natural biotopes and agricultural landscapes of the Tashkent Region, Uzbekistan - Bunyod N. Ganiev; Nodirjon N. Azimov; Bakhtiyor R. Kholmatov (Acta Biologica Sibirica, 2024)
Between 2014 and 2022, a comprehensive analysis was conducted to compare the spring diversity of avifauna, including bird occurrence, density, similarity, and differences between natural biotopes and agrarian landscapes in the Tashkent region. This study assessed changes in avifauna composition resulting from the conversion of natural biotopes into cultivated areas and evaluated the influence of anthropogenic factors on bird behavior. During the spring months of March, April, and May, approximately 205 bird species were recorded. Of these, 186 species were observed in natural biotopes, while 162 species were identified in agrarian landscapes. Notably, 143 species were common to both biotopes, whereas 43 species were exclusive to natural biotopes, and 19 species were found only in agrarian landscapes. The spring avifauna was classified into six categories based on their occurrence: Resident (51 species), Breeding-Migratory (75 species), Migratory-Wintering (34 species), Migratory (25 species), Breeding-Migratory-Wintering (11 species), and Wintering (9 species). The study included a comparative evaluation of bird diversity in natural biotopes and agrocenoses.